Answer: n=
−z2−5
z
Explanation:
Let's solve for n.
(−n)(z)−z2−2=3
Step 1: Add z^2 to both sides.
−nz−z2−2+z2=3+z2
−nz−2=z2+3
Step 2: Add 2 to both sides.
−nz−2+2=z2+3+2
−nz=z2+5
Step 3: Divide both sides by -z.
−nz
−z
=
z2+5
Answer:
-z^2-5z
To evaluate a polynomial at a given value, we substitute the given value for the variable and then simplify using order of operations. We are given n=3, so we substitute 3 for n in the polynomial −nz−z2−2z and simplify as follows.
−nz−z2−2z
−(3)z−z2−2z
−3z−z2−2z
−z2−5z
5.6m questions
7.3m answers